Impression Cytology as a Method of Cytological Diagnostics in Ophthalmology. Literature Review - I. A. Zlobin; S. V. Churashov; A. N. Kulikov; V. S. Chirsky; V. F. Chernysh; I. O. Gavrilyuk (Oftalʹmologiâ)
Impression cytology (from the Latin impressio — impact, indentation) is a minimally invasive method of cytological examination of the surface epithelium of the cornea, limbus and conjunctiva using various sorbing applicators for the collection of cellular material. The spectrum of diseases, in the diagnosis of which impression cytology is traditionally used, is mainly associated with pathological processes occurring in the conjunctiva. Such diseases as: Sjogren’s syndrome, dry eye syndrome, mucopolysaccharidosis, vitamin A deficiency, trachoma, squamous cell neoplasia of the ocular surface, etc. With the advent of the concept of limbal epithelial stem cell, new diagnostic possibilities of impression cytology in ophthalmology occurred.